2019
DOI: 10.1038/s41598-019-45197-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six blood-based age prediction models using DNA methylation analysis by pyrosequencing

Abstract: DNA methylation has been identified as the most promising molecular biomarker for the prediction of age. Several DNA methylation-based models have been proposed for age prediction based on blood samples, using mainly pyrosequencing. These methods present different performances for age prediction and have rarely, if ever, been evaluated and intercompared in an independent validation study. Here, for the first time, we evaluate and compare six blood-based age prediction models (Bekaert 1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
82
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 30 publications
5
82
1
4
Order By: Relevance
“…To our knowledge, only a single-locus model based on two CpGs of the ELOVL2 promoter and multiple linear regression has been proposed to date, in which the MAD of age predictions were of 5.03 and 5.75 in the training (303 samples) and testing (124 samples) sets respectively 25 . Despite multi-locus age prediction models generally presented better age prediction accuracy than the ELOVL2 single-locus model in their original studies, our recent study evaluating six blood based age prediction models using DNA methylation analysis by pyrosequencing showed that the performances of multi-locus models could sometimes be poorer in independent validation studies 26 . This could be attributed to inter-laboratory variations and discrepancies resulting from slight experimental differences accumulated during the different stages of sample processing, which could potentially increase as the number of PCR and pyrosequencing assays increases 26 .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…To our knowledge, only a single-locus model based on two CpGs of the ELOVL2 promoter and multiple linear regression has been proposed to date, in which the MAD of age predictions were of 5.03 and 5.75 in the training (303 samples) and testing (124 samples) sets respectively 25 . Despite multi-locus age prediction models generally presented better age prediction accuracy than the ELOVL2 single-locus model in their original studies, our recent study evaluating six blood based age prediction models using DNA methylation analysis by pyrosequencing showed that the performances of multi-locus models could sometimes be poorer in independent validation studies 26 . This could be attributed to inter-laboratory variations and discrepancies resulting from slight experimental differences accumulated during the different stages of sample processing, which could potentially increase as the number of PCR and pyrosequencing assays increases 26 .…”
Section: Discussionmentioning
confidence: 92%
“…Several multi-locus age prediction models based on DNA methylation of blood or other body fluids relied on less than a dozen markers using mainly pyrosequencing to several tens or hundreds of loci using epigenotyping arrays 12,21,26 . To our knowledge, only a single-locus model based on two CpGs of the ELOVL2 promoter and multiple linear regression has been proposed to date, in which the MAD of age predictions were of 5.03 and 5.75 in the training (303 samples) and testing (124 samples) sets respectively 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations